Resenha: OLIVEIRA, Ariovaldo Umbelino de. et al. Território em conflito, terra e poder. Goiânia: Kelps, 2014. 280p. - Ferreira, Gustavo Henrique Cepolini (Revista Cerrados, 2017)
Resenha: OLIVEIRA, Ariovaldo Umbelino de. et al. Território em conflito, terra e poder. Goiânia: Kelps, 2014. 280p.